UPAYA TIONGKOK MENERAPKAN IDE GREAT WALL IN THE SKY - Sulistyawati, Ida Ayu Surya; Fasisaka, Idin; Widya Nugraha, A.A Bagus Surya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2018)
ABSTRACT China is a country which has been concerned about their country's air security. Early in 2009, China began to focus its national security through air security. China established an idea of Great Wall in the Sky in 2009 to build and improve China air security. This research discussed by answering the question to how China`s strategy to implement the idea of Great Wall in the Sky. Data for this research were collected from various sources including: literary sources, journals and reports. Data were describe with Geopolitical View and National Security Strategy concept. By using qualitative method, this research shows that China is trying to strengthen its military army air force posture to implement the idea of Great Wall in the Sky. China takes advantage of the air space for raising its national security which is influenced by Geopolitical View and made some strategies based on the National Security Strategy. Keywords: Geopolitics, Air Security, Air Military Force, Security Strategy